Studi Awal Pengembangan Media Pembelajaran Komik Elektronik Pada Peserta Didik Kelas X MIPA SMA - Rini Dwi Lestari; Nurkhairo Hidayati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to find out how class X MIPA SMA students respond to learning media during the learning process. The learning media that will be developed is electronic comics for class X MIPA students at SMA Negeri 2 Pekanbaru. The data obtained from the student response sheet had a result of 79.76%, which was categorized as students agreeing with the learning media indicators. Based on these results, it can be concluded that learning media is really needed when the learning process is carried out.